The legal Framework for employee inventions - saad, amira; boukemidja, nadjiba (The journal of Teacher Researcher of Legal and political Studies, 2025)
This study addresses the legal framework governing inventions developed by employees in the context of their employment. The topic has gained notable relevance with the rapid expansion of technological innovation, which has intensified debates on how to clearly allocate rights arising from employee-generated inventions. The research examines the principal legislative approaches adopted to define the respective rights and obligations of employers and employee-inventors, with a view to ensuring a fair and effective legal balance between the parties. Particular emphasis is placed on the position adopted by the Algerian legislator, especially concerning the attribution of exclusive rights resulting from such inventions and the criteria used to determine whether these rights should vest in the employer or remain with the employee who created the invention.